Ejercicios isométricos para el fortalecimiento muscular de miembros inferiores en pacientes geriátricos de la asociación de discapacitados de Chimborazo. - Decimavilla Quinto, Helen Mabel (2017)
During the process of aging of the human being, biological, physiological and anatomical changes are developed, for this research, the modification suffered by the lower limbs at the muscular level was taken, due to these effects are interpreted into a decrease in muscle strength which it is reduced mostly at this stage. The research was carried out in the Asociaciòn de Discapacitados de Chimborazo; it includes a sample of 23 geriatric patients, an initial and final physiotherapeutic evaluation was performed to determine the muscular strength of the lower limbs. The objective was to use isometric exercises using the Troisier technique for the muscular strengthening lower limbs, starting from performing very simple exercises and evolve far more complex. The research was a descriptive and explanatory type with field and documentary design, once the isometric exercises were applied, it was verified by means of the final test of muscular strength for lower limbs to get up and sit in the chair, that the patients obtained higher muscle strengthening of your lower limbs checking the effectiveness of this treatment, for that reason it was suggested these exercises are implemented to senior citizens who come to this Association as support activities to the individual treatment that each one receives. In addition, articular functionality was recovered in some movements and pain was reduced by checking the EVA analog scale or pain scale and the goniometric assessment showing the effectiveness of the isometric exercises.